Pengembangan Strategi Pelayanan Perijinan Impor Produk Hortikultura Berbasis Teknologi Informasi di Kementerian Perdagangan - Deden Taufik Komara; Musa Hubeis; Muhammad Syamsun (Institut Pertanian Bogor, 2015)
Trade Facilitation Agreement mandates each member of the World Trade Organization (WTO), including Indonesia, to simplify the trade system in order to facilitate trade flows between countries. Inatrade is an information technology-based system that was built by the Ministry of Trade that aims to provide services of export and/or import procedure fastrer and more transparent. In order to determine the effectiveness of Inatrade services, it is necessary to identify the dominant factors, actors, and indicators that influence to the improvement of the service quality. This study aims to determine the conditions of service horticultural products import license, to identify the dominant factors, actors, and indicators which influence services, and to formulate strategies needed to improve the quality of licensing services at the Ministry of Trade. The research used analytical tools of Internal Factor Evaluation Matrix (IFE), External Factor Evaluation Matrix (EFE), SWOT and Analytical Hierarchy Process (AHP). Based on the result analiysis it was concluded that the licensing mechanism based integrated information technology and monitoring and evaluation system regularly including aspects of the systems, human resources and legal basis as a best strategy to improve the quality of services.